GOOD PUBLIC SERVICE PROFILE AND QUALITY IN THE SAMSAT OFFICE OF MALUKU PROVINCE - Zainal Abidin Rengifurwarin (Universitas Padjadjaran, 2022)
This research aims to analyze and describe the profile of good and quality public services at the Samsat of Maluku Province. The problems in this research are: (1) How is the profile of good public service at the Samsat of Maluku Province?. The respondents of this research were 59 people who were considered to have closeness and clear knowledge of the data and information needed at the research location. To collect the data needed in this research, a list of questions with a scale of 4 from Likers was used. The data collected from the field were processed and analyzed using non-parametric statistical techniques. The finding of this research shows that the Samsat of Maluku Province has practiced the good and quality public services. However, there are some notes that need to be considered in order to realize the maximum profile of good and quality public services.